Traditional leadership, democratic authority and public opinion in Botswana - Mpule, Keneilwe P (Department of Political Studies, 2015)
Renewed scholarly interest on chieftaincy hardly pays attention to the interaction between traditional leadership and modern democratic citizens. It is the state-chieftaincy relationship that has dominated much of the current research on traditional leadership in modern Africa. Even work that has been done on traditional leadership and the modern democratic state is mostly qualitative and speculative. This has led to the field being flooded by mostly qualitative and speculative assumptions on traditional rule. Botswana has not been immune to this anomaly. By employing public opinion data from the Afrobarometer surveys of 1999, 2003, 2005 and 2008, the study hopes to contribute towards the limited empirical research on traditional leaders, particularly in Botswana, which will make a valuable contribution to a more profound and grounded picture of traditional leadership in an era of heightened democratization resulting from economic development and modernization.